Peran Manajemen Keselamatan dan Kesehatan untuk Mencegah Kecelakaan Kerja: Literature Review - Dinda Nur Aprillya; Azly Febryan Tahri; Sindy Eka Rifani; Daud Arifin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to examine the role of occupational safety and health (OSH) management in preventing workplace accidents through a literature review approach. The method used is a literature review of various national and international journals published between 2018 and 2025. The results of the study indicate that structured and systematic OSH management can significantly reduce the risk of workplace accidents across various industrial sectors. Factors influencing the effectiveness of OSH management include workplace safety training, the use of personal protective equipment (PPE), consistent supervision, and the implementation of a workplace safety culture within the organization. Additionally, the integration of modern technology such as Virtual Reality (VR) in OSH training enhances workers' understanding and compliance with safety procedures. This study also highlights challenges in implementing OSH, such as low worker awareness and weak internal supervision. Therefore, strong managerial commitment and a collaborative approach are needed to build a sustainable workplace safety system. The findings from this research are expected to serve as a reference for developing more effective OSH strategies to create a safe and productive work environment.